Nanostructure and Nanomechanics of Prorocentrum donghaiense and Their Changes Under Nitrogen Limitation by Atomic Force Microscopy - He, Liyan; Yu, Zhiming; Zhu, Jianan; Cao, Xihua; Song, Xiuxian (Frontiers in Marine Science, 2022)
In this paper, atomic force microscopy was employed to study the harmful algal bloom species Prorocentrum donghaiense for the first time. Cells were immobilized in pores of polycarbonate membrane to keep moist and to acquire images of P. donghaiense at different scales. Typical ultrastructures, such as knob-like spines and valve pores, were observed on cell surfaces. These structure had similar characteristics to those observed on scanning electron microscopy images. What is more, the height and spacing of typical nanostructure, and nanomechanical parameters such as adhesion and elasticity, were also quantified by AFM. Additionally, the changes in cell surface nanostructure and nanomechanical characteristics under nitrogen limitation were further studied. Compared with the cells under normal culture conditions, the cell surface roughness and adhesion decreased, and the elastic modulus increased for cells under nitrogen limitation. Potential changes in the ability of P. donghaiense cells to perform normal physiological functions are reflected by changes in cell surface parameters, including cell surface roughness, cell surface adhesion and cell surface elasticity. The results of this study reveal how P. donghaiense responds to changes in the external environment under approximately physiological conditions from the perspective of changes in cell surface nanostructures and nanomechanical characteristics and provide a new understanding of its cell biology.